Comparing the performance of aerobic granular sludge versus conventional activated sludge for microbial log removal and effluent quality: Implications for water reuse. (15th November 2018) - Thwaites, Benjamin J.; Short, Michael D.; Stuetz, Richard M.; Reeve, Petra J.; Alvarez Gaitan, Juan-Pablo; Dinesh, Nirmala; van den Akker, Ben
Abstract: The application of aerobic granular sludge (AGS) technology has increased in popularity, largely due to the smaller physical footprint, enhanced biological nutrient removal performance and ability to perform with a more stable operation when compared to conventional activated sludge (CAS) systems. To date, the ability of AGS to remove microbial pathogens such as; Escherichia coli, Giardia, and Cryptosporidium has not been reported. This study compared the log10 removal performance of commonly used pathogen surrogates (sulfite-reducing clostridia spores, f-RNA bacteriophage, E. coli and total coliforms) by AGS and CAS during the start-up phase, through to maturation. Results showed that AGS performed as well as CAS for the log10 removal performance of all microbial surrogates, except for spores which were removed more effectively by AGS most likely due to greater adherence of spores to the AGS biomass compared to CAS mixed liquor. Results suggest that AGS is capable of meeting or exceeding CAS-equivalent health-based targets for pathogen removal in the context of water recycling as well as not adversely affecting the secondary effluent water quality (suspended solids, turbidity and particle size) in terms of ultraviolet light transmissivity (254 nm). These findings confirmed for the first time that the adoption of AGS operation would not adversely impact downstream tertiary disinfection processes from altered water quality, nor would it require further pathogen treatment interventions in addition to what is already required for CAS systems. Graphical abstract: Image 1 Highlights: Microbial LRV validation of AGS was conducted during start-up and mature operation. LRV was assessed for four indicators and compared to Conventional Activated Sludge. Start-up of AGS did not reduce microbial indicator LRV performance. AGS is able to meet or exceed CAS health-based targets for pathogen removal. Effluent quality from AGS is unlikely to impact downstream disinfection processes.